Concussion rescue eaudiobook A comprehensive program to heal traumatic brain injury. - Chapek, Kabran (HighBridge Audio, 2020)
With a foreword by #1 New York Times bestselling author, Daniel Amen, Concussion Rescue gives listeners the natural and effective protocols for healing from traumatic brain injury. In Concussion Rescue, Dr. Kabran Chapek shares the programs and protocols that he uses at the Amen Clinics to put patients on the pathway to healing from traumatic brain injury. From general assessment using sophisticated tools (SPECT imaging, MRIs and CAT scans) to very specific blood tests (out-of-balance lab values in blood can point to symptoms of brain injury and may explain why the brain is not healing), Dr. Chapek guides listeners to getting the proper medical care. He shares the cutting edge and most effective treatments for acute traumatic brain injury, as well as chronic traumatic brain injury, and provides the most powerful natural treatments. Concussion Rescue will be an invaluable and potentially lifesaving resource for athletes, parents of student athletes, coaches, and anyone who suffers a mild or severe brain injury.